Can corporate executives’ educational background in the digital economy promote corporate innovation? - Yuan, Yikun (Frontiers in Human Dynamics, 2025)
In recent years, the digital economy has developed rapidly. The following question arises: how do digital talents contribute to economic development? This study explores the role of digital talents from the perspective of corporate executives’ educational background in the digital economy. Based on the data of listed companies in the Shanghai and Shenzhen A-share markets from 2002 to 2020, this study examines the impact of corporate executives’ educational background in the digital economy on corporate innovation. The findings indicate that corporate executives’ educational background in the digital economy is positively related to corporate innovation. The results suggest that this effect occurs as a result of executives promoting digital transformation, understanding how to translate digital transformation into company innovation, and ultimately achieving improved productivity. The empirical conclusions contribute to the research on corporate executives and innovation, as well as providing a basis for government departments to formulate relevant policies to promote talent education.